Comparison of excursion-based approach with force-based approach in rehabilitation of repaired flexor tenons in zone ii and iii - Coates, Michelle Suzanne (My University, 2017)
This study explores the implementation of two different synergistic wrist motion approaches in the treatment of flexor tendon injuries, the excursion-based approach and the force-based approach. A prospective, quantitative, comparative intervention research design was used to compare the two approaches and determine their effectiveness in a public hospital in South Africa. The five participants’ range of motion, independence in activities of daily living and satisfaction levels were measured throughout the 12 week treatment programme. The excursion-based group showed significant improvement in passive Strickland and Glogovac scores over the rehabilitation period. The excursion-based group also achieved better final place-and-hold and active Strickland and Glogovac scores than the force-based group which showed a decline in these scores over the 12 weeks. Both groups had a poor result for active movement at the final session due to the development of adhesions, but were found to have an improvement in their upper limb function measured on the Disabilities of the Hand, Shoulder and Arm questionnaire in all activities except for those related to work. These results were not statistically significant. The poor results may be attributed to the unique challenges experienced by patients with flexor tendon injuries, living in under-resourced South African communities. The small sample and the fact that the excursion-based group received isolated flexor digitorum profundus tendon repairs while the force-based group received combined flexor digitorum profundus and flexor digitorum superficialis repairs may also have had an impact on the results. The outcomes of this study indicate that despite yielding successful results in research studies performed in developed countries, it is unlikely that either of these approaches will be suitable in the rehabilitation of patients with flexor tendon repairs in a public hospital in South Africa.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg in fulfillment of the requirements for the degree of Master of Science in Occupational Therapy Johannesburg, June 2017
Keywords: Flexor Tendon Rehabilitation